Generating some finite groups using sequential insertion systems - Yosman, Ahmad Firdaus; Fong, Wan Heng; Sarmin, Nor Haniza; Turaev, Sherzod (2017)
The operation of insertion in theoretical computer science has spurred much interest among researchers across many disciplines, where initially, it was introduced to generalize the concatenation operation. Previously, it was shown that a new variant of insertion, called sequential insertion systems with interactions, could generate all finite cyclic and dihedral groups. In this paper, we show that sequential insertion systems with interactions are also able to generate the quaternion group and all symmetric groups. We also determine the relation between sequential insertion systems with interactions and bonded sequential insertion systems.